Illiteracy, gender and high schooling in Jamaica - Miller, Errol L. (Institute of Social and Economic Research, UWI, 1996)
This study sought to determine whether access to the upper levels of educational system has an inspirational impact on achievement at the lower levels of the system. The results suggested that greater access to high schooling has had a positive effect on the improvement of literacy levels in Jamaica. It was also found that changes in the gender structure of teachers' colleges, primary school teaching, and the pupil-teacher system in the last decade of the 19th century had caused the reversal of traditional patterns of achievement, where boys performed better than girls. By the 1940s, in the black and coloured segments of Jamaican society, the younger females, particularly in rural areas, were participating more in the educational system and achieving at higher levels than the younger males
Keywords: Gender analysis